2011
DOI: 10.1089/end.2010.0648
|View full text |Cite
|
Sign up to set email alerts
|

Histotripsy Homogenization of the Prostate: Thresholds for Cavitation Damage of Periprostatic Structures

Abstract: Background and Purpose: Histotripsy is a noninvasive, pulsed ultrasound technology that produces mechanically homogenized tissue within targeted volumes. Previous work has demonstrated prostatic tissue debulking in a canine model. The aim was to establish safety thresholds by evaluating histologic changes of urinary sphincter, neurovascular bundle (NVB), and rectum after targeted histotripsy treatment of these critical structures. Materials and Methods: Rectum, urinary sphincter, and NVB in five anesthetized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 11 publications
(13 reference statements)
2
22
0
Order By: Relevance
“…Current treatment of meniscus or cartilage damage includes the intra-articular removal of damaged tissue with mechanical shavers 90,91 , saline jets 92 , and radiofrequency tools 90e92 . Ultrasound has been used to remove tissue by homogenization, debridement and/or thermal ablation 75,93 . Examples of these are debridement of meniscus 93 , corneal phacoemulsification 94 and thermal ablation of tumors in the prostate, breast, bone, brain, liver, and uterus 47 (Table II).…”
Section: Modification Of Soft Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Current treatment of meniscus or cartilage damage includes the intra-articular removal of damaged tissue with mechanical shavers 90,91 , saline jets 92 , and radiofrequency tools 90e92 . Ultrasound has been used to remove tissue by homogenization, debridement and/or thermal ablation 75,93 . Examples of these are debridement of meniscus 93 , corneal phacoemulsification 94 and thermal ablation of tumors in the prostate, breast, bone, brain, liver, and uterus 47 (Table II).…”
Section: Modification Of Soft Tissuementioning
confidence: 99%
“…Histotripsy is a technique where bubbles are collapsed and high speed fluid micro-jets disrupt tissue. In contrary to thermal HIFU approaches, histotripsy is based on introducing shear forces exceeding the fracture strength of the tissue at the site of the cavitation bubble cloud 75 . An advanced HIU surgical tool could image, cut, shape or ablate irregularities within the cartilage tissue using a noninvasive approach while avoiding heating problems within the tissue.…”
Section: Modification Of Soft Tissuementioning
confidence: 99%
“…[14][15][16][17] Efforts to translate this technology from the university research laboratory to the clinical setting necessitated the formation of a company, HistoSonics, Inc., where subsequent development and refinement resulted in creation of a clinical prototype named VORTX R X ® (Figure 1). The objective of this study was to assess local and systemic effects following prostate histotripsy using this prototype system in a canine model.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, the periprostatic neurovascular bundles and urinary sphincter were found to Departments of 1 Urology, be resilient to structural damage even at supratherapeutic histotripsy doses (up to 100k pulses targeted on a single point). 7 The histotripsy threshold for cavitational injury to the rectum was lower such that collagen disruption and hemorrhage were seen when >10,000 histotripsy pulses were applied directly to the rectal wall. 7 In this study, we sought to characterize the tissue effects and biologic response of the bladder trigone and ureteral orifices to direct application of histotripsy therapy.…”
mentioning
confidence: 99%
“…7 The histotripsy threshold for cavitational injury to the rectum was lower such that collagen disruption and hemorrhage were seen when >10,000 histotripsy pulses were applied directly to the rectal wall. 7 In this study, we sought to characterize the tissue effects and biologic response of the bladder trigone and ureteral orifices to direct application of histotripsy therapy.…”
mentioning
confidence: 99%